2022
DOI: 10.1038/s41467-022-34723-6
|View full text |Cite
|
Sign up to set email alerts
|

Specification of female germline by microRNA orchestrated auxin signaling in Arabidopsis

Abstract: Germline determination is essential for species survival and evolution in multicellular organisms. In most flowering plants, formation of the female germline is initiated with specification of one megaspore mother cell (MMC) in each ovule; however, the molecular mechanism underlying this key event remains unclear. Here we report that spatially restricted auxin signaling promotes MMC fate in Arabidopsis. Our results show that the microRNA160 (miR160) targeted gene ARF17 (AUXIN RESPONSE FACTOR17) is required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Compared with the 3‐day heat‐treated plants, the application of IAA–lanolin mixtures at concentrations of both 0.1 and 10 mg/g at the top of the first internode (the primary panicle was decapitated before treatment) significantly increased the number of apical tillers (Figure 7a–c,f). The polar auxin transporter inhibitor N‐1‐Naphthylphthalamic acid (NPA; Abas et al, 2021; Huang et al, 2022) appears to hinder the apical tiller formation, although not to a statistically significant extent (Figure 7a,d–f). It is noteworthy that treatment with the 10 mg/g of IAA–lanolin mixture significantly increased the leaf number per newly formed apical tiller, while the leaf number per apical tiller was significantly reduced when treated with the 10 mg/g of NPA–lanolin mixture (Figure 7g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the 3‐day heat‐treated plants, the application of IAA–lanolin mixtures at concentrations of both 0.1 and 10 mg/g at the top of the first internode (the primary panicle was decapitated before treatment) significantly increased the number of apical tillers (Figure 7a–c,f). The polar auxin transporter inhibitor N‐1‐Naphthylphthalamic acid (NPA; Abas et al, 2021; Huang et al, 2022) appears to hinder the apical tiller formation, although not to a statistically significant extent (Figure 7a,d–f). It is noteworthy that treatment with the 10 mg/g of IAA–lanolin mixture significantly increased the leaf number per newly formed apical tiller, while the leaf number per apical tiller was significantly reduced when treated with the 10 mg/g of NPA–lanolin mixture (Figure 7g).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that heat stress likely stimulates the apical tiller formation via affecting auxin biosynthesis or auxin signaling at the apex of sorghum. Notably, the application of the polar auxin transporter inhibitor NPA (Abas et al, 2021; Huang et al, 2022) seems to restrain the apical tiller formation, though not reaching statistical significance. It is possible that the plants could not efficiently absorb the NPA, prompting consideration of potential NPA injection into the plants for future experimentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two well‐known primary miRNA processing factors, SE and HYL1 , were identified in the list of BZR1 target genes. We therefore decided to focus on SE , HYL1 , and DCL1 , as the roles of miRNAs in MMC specification were recently reported (Huang et al ., 2022). qRT‐PCR analysis showed that the transcript level of SE , HYL1 , and DCL1 was significantly reduced in sex‐1 sextuple mutant compared with WT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, although several regulatory factors for both generations were identified in sexual models (Nakajima, 2018;Hisanaga et al, 2019;Pinto et al, 2019;Lora et al, 2019;Hater et al, 2020;Khanday & Sundaresan, 2021;Kim et al, 2021;Vigneau & Borg, 2021;Y. Li et al, 2021;Cai et al, 2022;Huang et al, 2022;Petrella Ó 2023 The Authors New Phytologist Ó 2023 New Phytologist Foundation New Phytologist (2023) 240: 597-612 597 www.newphytologist.com This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited. Sanchez-Vera et al, 2022), no clear hookup with natural apomictic systems has emerged yet, except evidence for members of the RNA-directed DNA methylation pathway (Grimanelli, 2012;Selva et al, 2017;Galla et al, 2019).…”
Section: Introductionmentioning
confidence: 99%